Synthesis, characterization and application of hollow titania microspheres containing silver and gold nanoparticles in the photodegradation of pesticides - Baharvand, Afrouz (2015)
Hollow titania (TiO2) materials have unique properties, such as multiple light reflection and diffraction, surface permeability, light-harvesting capability and their technological importance in the fields of medicine, pharmacy, materials science, water treatment, catalyst and photocatalyst. The research described in this dissertation is a comprehensive account of an attempt to correlate structural and physicochemical properties of hollow TiO2 microspheres containing silver (Ag) and gold (Au) nanoparticles with their photocatalytic properties. It is hypothesized that hollow TiO2 microspheres containing Ag and Au nanoparticles can enhance light harvesting and also facilitates the charge separation, in the photodegradation of pesticides. The location of Ag and Au, whether inside or outside the hollow titania, may also affect the photocatalytic activity. The synthesis of hollow TiO2 microspheres containing Ag or Au nanoparticles was conducted by using fructose as the precursor via hydrothermal method. The fructose-derived carbonaceous spheres obtained were then used as the template for the synthesis of hollow crystalline TiO2 microspheres photocatalysts. These photocatalysts were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, diffuse reflectance ultraviolet–visible (DR UV–Vis) spectroscopy, photoluminescence (PL) spectroscopy, thermogravimetry (TG) analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption and chemical analysis by X-ray fluoresence (XRF) spectroscopy. TiO2 photocatalyst obtained was in the crystalline anatase phase and spherical in shape, with cavity inside the spheres. The existence of Ag and Au was confirmed by XRD, XRF, EDX, TEM and HRTEM. DR UV–Vis spectra revealed that the hollow TiO2 containing noble metals have absorption spectrum in a longer wavelength in comparison to that of commercial TiO2. By employing pesticides, namely paraquat dichloride, diazinon, imazalil sulfate, atrazine, lindane and chlorpyrifos, as the target compounds, the photocatalytic activity investigation of the hollow TiO2 microspheres was carried out. The photodegradation of pesticides over hollow TiO2 microspheres containing Ag or Au nanoparticles was correlated with the type of pesticides in the following decreasing order: chlorpyrifos ? diazinon ? ?lindane ? imazalil sulphate ? paraquat dichloride ? atrazine. It was also observed that the location of Ag or Au, whether inside or outside the microspheres, is an important factor to achieve high photocatalytic activity for the decomposition of pesticides. The photocatalytic activity results revealed that the attachment of Ag nanoparticles outside the TiO2 microspheres was the most effective location in the photodegradation of these pesticides, with 84% degraded. Based on the above results, it is suggested that the location of the Ag or Au as electron scavengers on the hollow TiO2 microspheres plays an important role in the photocatalytic activities of these materials.